2019
DOI: 10.1039/c9ce00781d
|View full text |Cite
|
Sign up to set email alerts
|

Drug–drug salts of mefenamic acid\tolfenamic acid and piperazine to improve physicochemical properties for potential veterinary use

Abstract: Drug–drug salts of mefenamic acid\tolfenamic acid and piperazine were designed to improve the solubility and hygroscopicity, which could possibly extend the drug–drug salt form into veterinary use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…In addition to improving the solubility, a typical physicochemical property, crystal engineering may provide other benefits by employing different cocrystal/salt formers, such as a pleasant taste, hepatoprotective effects, and multiple curative efficacies. It has been demonstrated that phenolic acids have some positive pharmacology activities. Especially, the antifungal and anti-inflammatory activity of these phenolic acids may bring an enhanced therapeutic effect and reduce the risk of hepatotoxicity at the same time. In recent years, the applicability of phenolic acids as potential cocrystal/salt formers has been widely reported.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to improving the solubility, a typical physicochemical property, crystal engineering may provide other benefits by employing different cocrystal/salt formers, such as a pleasant taste, hepatoprotective effects, and multiple curative efficacies. It has been demonstrated that phenolic acids have some positive pharmacology activities. Especially, the antifungal and anti-inflammatory activity of these phenolic acids may bring an enhanced therapeutic effect and reduce the risk of hepatotoxicity at the same time. In recent years, the applicability of phenolic acids as potential cocrystal/salt formers has been widely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Conformational analysis was carried out to indicate which conformations of a molecule with flexible groups were adopted within the crystal. The overlay of TM on the benzene ring is shown in Figure a. Two arms of TM can rotate around C-N near the benzene ring; interactions on the thioureido can be monitored by the dihedral angle of C 8 –C 9 –N 3 –C 10 .…”
Section: Resultsmentioning
confidence: 99%
“…Pharmaceutical cocrystallization provides great convenience for optimizing the physicochemical properties of solid drugs, including their stability, dissolution rate, permeability and mechanical properties, without changing their molecular structures and pharmacological activity. [14][15][16][17][18][19][20] Moreover, both salts and cocrystals tremendously expand the solid-state scope of drugs, which present non-negligible intellectual property value. 21 Different solid forms always demonstrate different physicochemical properties, which further affect the production process and efficacy of drugs.…”
Section: Introductionmentioning
confidence: 99%